Comparison of Bone Prefabrication with Vascularized Periosteal Flaps, Hydroxyapatite, and Bioactive Glass in Rats - Ersoy, Burak; Bayramiçli, Mehmet; Ercan, Feriha; Şirinoğlu, Hakan; Turan, Pınar; Numanoğlu, Ayhan (Journal of Reconstructive Microsurgery, 2015)
Background Periosteal flaps possess osteoprogenitor cells and an osteoinductive potential that can be further augmented by combination with a biodegradable scaffold; therefore, various osteoconductive and osteostimulative biomaterials are frequently combined with periosteal flaps in studies of bone prefabrication. An experimental study was designed to determine and compare the contribution of bioactive glass and hydroxyapatite to osteoneogenesis in rats when combined with a periosteal flap.Materials and Methods In 60 Sprague Dawley rats, saphenous artery periosto-fasciocutaneous island flaps were transposed to abdomen. In group 1, the flap was left alone, in group 2, an empty artificial pocket made of Gore-Tex (W. L. Gore & Associates, Inc.; Flagstaff, AZ) was sutured onto the periosteal layer, and in groups 3 and 4, the pocket was filled with bioactive glass and hydroxyapatite, respectively. Following sampling for histological analysis, a 4-point scoring system was used to grade inflammatory cell infiltration, osteogenesis, angiogenesis, and cell migration into the bioactive material.Results The combination of the periosteal flap with any of the bioactive materials resulted in significantly higher percentages of animals exhibiting osteogenesis (80% in hydroxyapatite group and 93.3% in the bioactive glass group; p = 0.0000528) and angiogenesis. Comparison of the bioactive material groups revealed that a significantly higher proportion of animals in the bioactive glass group exhibited moderate or severe inflammation (80 vs. 20%; p = 0.002814).Conclusion Periosteal flaps prefabricated with hydroxyapatite or bioactive glass in rats exhibit osteogenic capacities that are not dependent on direct bone contact or proximity to vascular bony tissue. The innate capacity of the periosteal flap when utilized alone for osteoneogenesis was found to be rather insufficient.
Keywords: hydroxyapatite; bioactive glass; periosteum; rats; osteogenesis